Penegakan Hukum Administrasi Terhadap Izin Usaha Perkebunan Budidaya Di Kabupaten Seram Bagian Timur - Kohilay, Puan Yulistiana; Nirahua, Salmon Eliazer Marthen; Bakarbessy, Andress Deny (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The government of East Seram district issued a nutmeg cultivation business permit to CV Sumber Berkat Makmur which was carried out in Sabuai village, Siwalalat district, East Seram district, by not activating the supervisory function and applying sanctions.Purposes of the Research: Analyzing and reviewing how the East Seram district government should enforce administrative law on permits that have been issued. Methods of the Research: This research is included in normative legal research, namely research examining various positive legal provisions, various legal principles, legal principles and doctrines in order to answer the legal issues at hand.Results of the Research: The government of East Seram district issued a business license for nutmeg cultivation in Sabuai village, Siwalalat district, East Seram district, after the permit was issued the government did not exercise its authority based on the applicable laws and regulations. In addition, the SBT government as the permit issuer also implements sanctions in the form of revocation of business licenses but this is not in accordance with the procedures for applying sanctions in existing laws and regulations.